A science of signs study on the Iban Bunga Terung as: a cultural identity - Sonny Jumpo; Mohammad Puad Bebit (International Journal of Current Research, 2021)
Tattoos add a perceived aesthetic value to the body of the wearer. In instances where tattoos are worn – by choice – to enhance the outer appearance of the wearer, they are a vivid expression of artistic freedom, individualism and even a mark of belonging. For the same reasons that their appearance becomes conspicuous, tattoo wearers are vulnerable to receive negative first impressions. Tattoos are broadly divided into three types: those that are of tribal origins, those that are linked with criminal communities, and those that are forcefully given to mark prisoners or given as punishment. A well-known example of tribal tattoo are the ones worn by Borneo Ibans. This paper will explain the importance of semiotics studies by looking at the cultural value of a particular tribal tattoo. The terung is an Iban tattoo that a man will get when he goes for bejalai, a journey comparable to a walkabout. The theory of semiotics and representation by Charles Sanders Peirce will cover the knowledge process towards understanding the bunga terung. This research will enable us to differentiate between a tattoo that represents a particular indigenous community and a tattoo that represents a criminal one.